2018
DOI: 10.1002/wrna.1511
|View full text |Cite
|
Sign up to set email alerts
|

The complex enzymology of mRNA decapping: Enzymes of four classes cleave pyrophosphate bonds

Abstract: The 5 0 ends of most RNAs are chemically modified to enable protection from nucleases. In bacteria, this is often achieved by keeping the triphosphate terminus originating from transcriptional initiation, while most eukaryotic mRNAs and small nuclear RNAs have a 5 0 !5 0 linked N 7 -methyl guanosine (m 7 G) cap added. Several other chemical modifications have been described at RNA 5 0 ends. Common to all modifications is the presence of at least one pyrophosphate bond. To enable RNA turnover, these chemical mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 168 publications
(276 reference statements)
0
41
0
Order By: Relevance
“…Several studies indicate that DCP2 appears to target distinct transcripts and the reported targets are almost all mRNAs. [40,45,46] However, we observed that DCP2 can bind to WFDC21P, a long non-coding RNA, to participate in cancer pathogenesis. We further clari ed that WFDC21P degradation played important roles in the tumorigenesis of lung carcinoma, and showed that DCP2 directly regulated by miR-4293, down-regulated WFDC21P expression.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies indicate that DCP2 appears to target distinct transcripts and the reported targets are almost all mRNAs. [40,45,46] However, we observed that DCP2 can bind to WFDC21P, a long non-coding RNA, to participate in cancer pathogenesis. We further clari ed that WFDC21P degradation played important roles in the tumorigenesis of lung carcinoma, and showed that DCP2 directly regulated by miR-4293, down-regulated WFDC21P expression.…”
Section: Discussionmentioning
confidence: 88%
“…The discovery of NAD-capped RNAs in bacteria [3,8,9], mammalian cells, yeast [11,18] and plants [12,13] highlights the importance of studying the biogenesis, function, and removal of novel 5'-RNA modifications. The identification of new decapping enzymes can make important contributions to understanding the biological roles of NAD-capped RNAs [50].…”
Section: Discussionmentioning
confidence: 99%
“…eol-1 encodes a decapping exoribonulease orthologous to yeast Rai1 and mammalian DXO ( Figure 2B). Mammalian DXO processes the 5' end of mRNA (Kramer and McLennan, 2019), including a decapping activity that removes the unmethylated guanosine cap and the first nucleotide (GpppN), the deNADing activity that removes the nicotinamide adenine dinucleotide (NAD) cap, the pyrophosphohydrolase (PPH) activity that releases pyrophosphate (PPi) from 5' triphosphorylated RNA, and 5'-3' exonuclease (5'-3' Exo) to degrade the entire RNA ( Figure 2C). The removal the m 7 G cap and subsequent degradation of mammalian mRNAs are directed by the decapping exoribonuclease DXO.…”
Section: Eol-1 Acts Downstream Of Drh-1 For Somatic Silencingmentioning
confidence: 99%